2021
DOI: 10.1515/cllt-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring semantic differences between the Indonesian prefixesPE-andPEN-using a vector space model

Abstract: Indonesian has two prefixes, PE- and PEN-, that are similar in form and meaning, but are probably not allomorphs. In this study, we applied a distributional vector space model to clarify whether these prefixes have discriminable semantics. Comparisons of pairs of words within and across morphologically defined sets of words revealed that cosine similarities of pairs consisting of a word with PE- and a word with PEN- were reduced compared to pairs of only PE- words, or of only PEN- words. Furthermore, nouns wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Shen and Baayen (2021) find that semantic transparency measured by DS is linked to the productivity of adjective-noun compounds in Mandarin. DS models used in investigating the paradigmatic relation between two Indonesian prefixes (Denistia, Shafaei-Bajestan, & Baayen, 2021) corroborated the findings of earlier corpus-based analyses. The discriminative lexicon model of Baayen, Chuang, Shafaei-Bajestan, and Blevins (2019) is a computational model of lexical processing, including morphologically complex words, that incorporates insights from distributional semantics for the representation of word meanings.…”
Section: Introductionsupporting
confidence: 75%
“…Shen and Baayen (2021) find that semantic transparency measured by DS is linked to the productivity of adjective-noun compounds in Mandarin. DS models used in investigating the paradigmatic relation between two Indonesian prefixes (Denistia, Shafaei-Bajestan, & Baayen, 2021) corroborated the findings of earlier corpus-based analyses. The discriminative lexicon model of Baayen, Chuang, Shafaei-Bajestan, and Blevins (2019) is a computational model of lexical processing, including morphologically complex words, that incorporates insights from distributional semantics for the representation of word meanings.…”
Section: Introductionsupporting
confidence: 75%
“…Based on the keywords associated with ads and the script associated with the video, the vector space model (VSM; Denistia et al, 2021) is a particularly popular choice for ad matching. In VSM, the similarity between documents italicDocx and italicDocy, RDocxDocy is calculated from the cosine of the angle between two vectors: RDocxDocy=ωDocxωDocyωDocx×ωDocy, where ωDocx and ωDocy are the weight vectors of italicDocx and italicDocy, respectively.…”
Section: Computer Science Studiesmentioning
confidence: 99%
“…Therefore, a set of databases are needed to explore this phenomenon from the quantitative perspective. Recent studies on these prefixes conducted analyses based on corpus data (Denistia & Baayen, 2019, 2022a, 2022b, Denistia et al, 2022. Their research focused on investigating whether PE-and PEN-are allomorphs from their productivity, computational learning, and semantics distribution respectively.…”
Section: Introductionmentioning
confidence: 99%
“…PE-, however, is an outlier in the linearity of the base words' productivity. Apart from productivity analysis, using semantics distribution (Mikolov et al, 2013), Denistia et al (2022) measured the similarity of all possible combination between PE-and PEN-. They found that PE-and PEN-are semantically discriminable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation